2013
DOI: 10.2139/ssrn.2331331
|View full text |Cite
|
Sign up to set email alerts
|

Pooling and Sharing Income within Households: A Satisfaction Approach

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
0
1
0
Order By: Relevance
“…We include a number of control variables in our model to account for individual characteristics that might affect individuals' wages. Our choice of control variables is related to the studies of Brunello and D'Hombres (2007), Larsen et al (2011), and Elsas (2021). Specifically, we control for working experience ( exper ijkt ), measured as the total number of years an individual has worked at the time of the survey.…”
Section: Methodsmentioning
confidence: 99%
“…We include a number of control variables in our model to account for individual characteristics that might affect individuals' wages. Our choice of control variables is related to the studies of Brunello and D'Hombres (2007), Larsen et al (2011), and Elsas (2021). Specifically, we control for working experience ( exper ijkt ), measured as the total number of years an individual has worked at the time of the survey.…”
Section: Methodsmentioning
confidence: 99%
“…The unitary model assumes that households have one utility function and one primary decision-maker who altruistically allocates the household resources to maximize utility. Under this model, household members have shared preferences and the same marginal utility of income (Elsas, 2013). Following the unitary model, the amount and composition of household expenditures depend only on the pooled incomes but not on who generates them (Abdullah Yusof & Duasa, 2010;Browning, Bourguignon, Chiappori, & Lechene, 1994).…”
Section: Models Of Household Behaviour and Household Expenditure Patt...mentioning
confidence: 99%
“…Doubts may arise if this result is driven by couples who live together but do not pool their income. In a study with nearly the same setup I analyzed this prerequisite and then restricted the income sharing regression to couples who reported to pool their incomes (Elsas 2013). Results of this research indicated that systematic satisfaction differences are attenuated in income pooling couples, but still present.…”
Section: A2 Supplementary Materials For Chapter 3 A21 Income Pooling ...mentioning
confidence: 99%